Multitafsir Materi Sastra pada Ujian Nasional: Studi Kasus di SMAN 8 Denpasar - I Gusti Ketut Tribana (Pusat Kajian Bali Universitas Udayana, 2014)
AbstractThis article gives an overview to the subject teachers of Indonesian language and literature on many questions regarding literary multiple interpretations. Also to determine the effect of the questions about literature that multiple interpretations of the results of the National Examination (UN). It also contributes ideas for discussion for teachers to better act, especially in answering the questions of literary material in the National Exam (UN) senior high school in Bali and Indonesia.